Cytotoxic activity of hantap (Sterculia oblongata Mast) leaves extract against breast cancer cells line (MCF7/HER2): the effect on the expression of HER2 mRNA and the apoptosis - Sitti Ayu Suhartina Yahya; Mustofa; Woro Rukmi Pratiwi; Adika Suwarman (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Hantap leaves (Sterculia oblongata Mast) has been used traditionally to treat breast cancer in Palu, Central Sulawesi. However, its use is just based on empirical evidences rather than scientific evidences. The study aimed to investigate the cytotoxic activity of hantap leaves extracts against breast cancer cells line. The effect of this extract on the HER2 expression and the apoptosis was also evaluated. The hantap (S. oblongata Mast) leaves extracts were prepared by consecutive maceration method using n-hexane, methanol and water, respectively. The cytotoxic activity against MCF7/HER2 breast cancer cells line was evaluated using the MTT assay with doxorubicin as a positive control. The HER2 mRNA expression was examined using RT-PCR and the apoptosis after 24 h incubation was examined using a fluorescence microscope after AO-PI (acridine orange-propidium iodide) staining. Among three extracts tested, the methanolic extract exhibited the most cytotoxic against MCF7/HER2 cells with an IC50 of 91.25 μg/mL. Therefore, the methanolic extract was subjected to further study. The methanolic extract at concentration of 1/2IC50; 1IC50 and 2IC50 μM induced 6.8; 26.3 and 25.3% apoptosis of the MFC7/HER2 cell lines, respectively. The methanolic extract at concentration of 1/2IC50; 1IC50 and 2IC50 μM inhibited HER2 mRNA expression to be 0.6; 0.25 and 0.33 compared to control cells. In conclusion, the methanolic extract of hantap leaves (S. oblongata Mast) has cytotoxic activity against MCF7/HER2 breast cancer cell lines by induce cells apoptosis and inhibit HER2 mRNA expression. Further study, will be conducted to isolate active constituents as anticancer.